Counselling young people : a handbook for trainees and practitioners - Porter, Louise (New York, NY : Routledge, 2024)
"Practical and clearly written, this new book from best-selling author Louise Porter equips mental health professionals with the knowledge and skills they need to provide insightful guidance and support to children and adolescents. The book introduces exciting new models for thinking about young people's needs, self-esteem and resilience that will invigorate counselling. It outlines the most common presenting difficulties for young people and provides clear, practical guidance on how professionals in a counselling environment can respond to these in an effective way. Offering a coherent blend of theories and practices, chapters address a wide range of emotional, social, behavioural and learning difficulties with which young people may present to counselling, such as experiences of grief and loss, anxiety and depression, disordered eating, and dealing with adversity. With an aim to empower, the book presents a non-pathologising approach to counselling that respects the skills that young people bring to working through their challenges. Accessible for professionals and trainees alike, this book is a must-have for anyone working in a counselling capacity with children and adolescents"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Youth -- Counseling of; Counselors -- Training of